'Shock Therapy' as a Neo-Liberal Response to an Economic Crisis. Issue 1 (2nd January 2016) - Kokushkin, Maksim; Pettys, Alicia M.
Abstract : This paper investigates the resurgence of neo-liberalism during and after the Great Recession by exploring shock therapy reforms in the American state of Michigan. Using the framework of variegated neo-liberalization we demonstrate that even failed neo-liberal policies can be reused in divergent geographical and historical contexts. Further, we suggest that the jurisdictional and territorial autonomy of the state of Michigan allows its government to initiate market disciplinary restructuring in some cases at the expense of potential solutions to the crisis. In this process, the federal state's government actively overrides local and city governments and their voters. The resulting new policy configurations continue and deepen structural changes that favour neo-liberal ideologies. Our most telling example is a unique new neo-liberal formation, emergency management, a legitimate institution that allows an appointed individual to suspend democratic procedures and dismiss democratically elected local officials under the premises of a crisis of governance. Since neo-liberalization works in non-linear, but cumulative ways, one could expect that the emergency management model can be replicated outside the state of Michigan or the USA. We conclude that the broad neo-liberal project has no problem suspending, circumventing, or removing democratic procedures in its continued metapowering effort to create lasting structural change.